2007
DOI: 10.1590/s0100-879x2006005000113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT1B receptor agonists injected into the prefrontal cortex on maternal aggression in rats

Abstract: Serotonin (5-HT 1B ) receptors play an essential role in the inhibition of aggressive behavior in rodents. CP-94,253, a 5-HT 1B receptor agonist, can reduce aggression in male mice when administered directly into the ventro-orbitofrontal (VO) prefrontal cortex (PFC). The objective of the current study was to assess the effects of two selective 5-HT 1B receptor agonists 129), microinjected into the VO PFC, on maternal aggressive behavior after social instigation in rats. CP-94,253 (0.56 µg/0.2 µL, N = 8, and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…A reduction in expression of the 5-HT 1B receptor, in the targeted region of the microinjection, is a plausible explanation for why Alc-naïve (de Almeida et al, 2006) and Alc-heightened aggressive mice (experiment 2) exhibit such profoundly different behavioral responses to intracortical CP-94,253 microinjections. Initially, the aggression-heightening effect of the 5-HT 1B agonist, CP-94,253, was surprising because it does not reflect the prevailing findings proposing an anti-aggressive role for this receptor Fish et al, 1999;Grimes and Melloni, 2005;Olivier and Van Oorschot, 2005;Bannai et al, 2007;Veiga et al, 2007). However, in addition to reductions in 5-HT 1B mRNA, Chiavegatto et al (2007) also found decreases in prefrontal mRNA transcript for 5-HT 1A , 5-HT 2A , 5-HT 2C , 5-HT 6 , and 5-HT 7 receptors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A reduction in expression of the 5-HT 1B receptor, in the targeted region of the microinjection, is a plausible explanation for why Alc-naïve (de Almeida et al, 2006) and Alc-heightened aggressive mice (experiment 2) exhibit such profoundly different behavioral responses to intracortical CP-94,253 microinjections. Initially, the aggression-heightening effect of the 5-HT 1B agonist, CP-94,253, was surprising because it does not reflect the prevailing findings proposing an anti-aggressive role for this receptor Fish et al, 1999;Grimes and Melloni, 2005;Olivier and Van Oorschot, 2005;Bannai et al, 2007;Veiga et al, 2007). However, in addition to reductions in 5-HT 1B mRNA, Chiavegatto et al (2007) also found decreases in prefrontal mRNA transcript for 5-HT 1A , 5-HT 2A , 5-HT 2C , 5-HT 6 , and 5-HT 7 receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, systemic administration of CP-94,253 reduces several forms of escalated aggressive behavior including Alc-, instigation-, and schedule-heightened aggression (Fish et al, 1999de Almeida et al, 2006;Bannai et al, 2007). However, the effects of local administration of CP-94,253 into the orbitofrontal cortex (OFC) are more complex and reveal that maternalinstigated aggression is insensitive to microinjection of CP-94,253 while species-typical aggression is potently reduced (de Almeida et al, 2006;Veiga et al, 2007). Together, these studies suggest that escalated and speciestypical aggression may share similar but not identical mechanisms and that the prefrontal cortex and 5-HT 1B receptors may importantly contribute to these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Nonselective 5-HT 1 receptor agonists (RU24969, eltoprazine) and recently developed 5-HT 1A receptor agonists alnespirone and S-15535 reduced aggression quite specifically and did not decrease social interest or exploration [de Boer et al, 1999[de Boer et al, , 2000de Boer and Koolhaas, 2005;Olivier et al, 1995]. The selective antiaggressive effect was described for 5-HT 2A receptor antagonist ritanserin [Sakaue et al, 2002], 5-HT 1A receptor agonists MKC-242 [Sakaue et al, 2001], 5-HT 1B receptor agonists anpirtoline, CP-94,253, and CP-93,129, 5-HT 1B/D receptor agonists zolmitriptan [de Almeida and Miczek, 2002;Veiga et al, 2007] and for 5-HT 1C agonist WAY-163909 [Rosenzweig-Lipson et al, 2007]. Similar selective antiaggressive effect was also observed for the selective vasopressin V1b receptor antagonist SSR149415 [Blanchard et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Central serotonin signaling is required for normal postpartum maternal behaviors in rodents (Angoa-Perez, 2014; Barofsky et al, 1983;Lerch-Haner et al 2008;Pawluski et al, 2012;Zhao and Li, 2010) and the mPFC may a site where it acts for these effects (see Afonso et al 2007;Febo, Felix-Ortiz, and Johnson, 2010;Pereira and Morrell, 2011;Veiga, Miczek, Lucion, and Alegre, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%